Determinants of consumers’ purchase intention to buy smartphones online - Mohammed Julfikar Ali; Md. Mobarak Karim; Benazir Ishaque Hitoishi; H. M. Atif Wafik; K. M. Anwarul Islam (Innovative Marketing)
In this technological era, online business is expanding due to increased internet conveniences. Smartphone users are drastically growing in Bangladesh, where it plays a vital role as a strong catalyst for economic development. On the other hand, the success of the online business is associated with creating online purchase tendency by determining influencing factors of consumers’ intention. The ultimate purpose of this paper is to identify the influential variables of consumers’ purchase intention to buy smartphones on online platforms. To fulfill the aim, a structured questionnaire has been elaborated based on the literature review to find this study’s objective. Cronbach’s alpha value was used to assess the inner surface of this study. The non-probability convenience sampling method and a 5% significance level are used to accept the hypotheses. Altogether, 350 survey questionnaires were distributed among the online-based social media customers, and finally, 288 responses were received genuinely, where the response rate was 82%. Henceforward, the sample size of the study is n = 288. SPSS version 26.0 has been applied to scrutinize hypothesis tests in this study. This paper also offers implications for online business people and several impactful guidelines for future research studies.